Biomarkers of exposure to nanosilver and silver accumulation in yellow perch (Perca flavescens). (7th November 2016) - Martin, Jonathan D.; Colson, Tash‐Lynn L.; Langlois, Valerie S.; Metcalfe, Chris D.
Abstract: There is a risk of exposure of aquatic organisms to silver nanoparticles (AgNPs) from discharges of municipal and industrial wastewater. In the present study, yellow perch ( Perca flavescens ) were exposed to environmentally relevant concentrations (1 mg/L and 100 mg/L) of AgNPs and silver ions (Ag + ) in static‐renewal experiments conducted over 96 h and 10 d. The greatest accumulation of total Ag occurred in the liver of P. flavescens, and there was >10‐fold more accumulation in the treatments with Ag + relative to the AgNP treatments. Residues of total Ag increased with concentration and duration of exposure in liver, gill, and muscle. Both exposures caused a 2‐fold induction of gene expression for metallothionein ( mt ) in liver tissue after 96 h of exposure and reductions in levels of oxidized glutathione (GSSG) in liver after 10 d of exposure. Both AgNPs and Ag + decreased the expression of heat‐shock proteins ( hsp70 ). Exposure to the high concentration of AgNPs for 10 d significantly increased lipid peroxidation in gill tissue, as indicated by the thiobarbituric acid reactive substances (TBARS) assay. There was a negative correlation between mean levels of GSSG and TBARS for both gill and liver tissue when data for all treatments were combined. It is significant that these biological responses were observed in P. flavescens exposed to AgNPs, even though accumulation of total Ag was at least 10‐fold lower relative to the treatments with Ag + . Environ Toxicol Chem 2017;36:1211–1220. © 2016 SETAC